Determination of total iron‐binding capacity of transferrin using metal organic framework‐based surface‐enhanced Raman scattering spectroscopy. (29th September 2020) - Das, Anupam; Choi, Namhyun; Moon, Joung‐Il; Choo, Jaebum
Abstract: We report the rapid and sensitive determination of the total iron‐binding capacity of transferrin (Tf) in human serum using surface‐enhanced Raman scattering (SERS) spectroscopy. Herein, metal organic framework (MOF)–gold nanoparticle (AuNP) complexes were used as the SERS substrate. The highly porous MOF preconcentrates the reporter molecules and accelerates the approach of the reporter molecules to the vicinity of the AuNPs on the surface of the MOF. As a result, a significant number of reporter molecules are trapped close to SERS‐active "hot spots, " and their Raman signals are greatly enhanced. Additionally, Tf acts as an anchor to form a three‐dimensional assembly of MOF–AuNP units via specific binding to the Fe(III) ions of adjacent MOF units when MOF–AuNP complexes are added to human serum. This leads to further enhancement of the Raman signals of Raman reporter molecules with increasing Tf concentration. Quantitative estimation of Tf is possible by monitoring the variations in the intensity of the Raman signal of Raman reporter molecules adsorbed on MOF–AuNP complexes as a function of the Tf concentration. In this work, SERS‐based analysis using the MOF–AuNP complexes was performed to determine the concentration of Tf in the human serum for diagnosing iron deficiency. The limit of detection of Tf was determined to be 0.51 μM in spiked human serum. This SERS‐based analysis of Tf using MOF–AuNPs provides new insight for the rapid and sensitive diagnosis of iron deficiency in human serum. Abstract : A new surface‐enhanced Raman scattering (SERS)‐active substrate, a metal organic framework (MOF)–gold nanoparticle (AuNP) complex, was fabricated by assembling citrate‐capped AuNPs on the surface of an amine‐functionalized MOF, MIL‐101(Fe)‐NH2 . The current SERS‐based analysis provides a conceptually new diagnostic platform for accurate determination of the total iron‐binding capacity (TIBC) of transferrin in human blood plasma samples.